Implementasi Terapi Mindfulness terhadap Environmental Mastery Warga Binaan di Lembaga Pemasyarakatan Perempuan Kelas IIA Tangerang - Maysahani Diya Faiz; Putri Dian Dia Conia; Puspa Pertiwi (Jurnal Pengabdian Masyarakat Nusantara, 2026)
Overcapacity in correctional facilities is a persistent issue that can generate psychological distress and reduce inmates’ ability to adapt effectively to their living environment. Limited personal space, restricted autonomy, and continuous social pressures may negatively affect environmental mastery, which is an important dimension of psychological well-being. This study aimed to examine the effectiveness of mindfulness therapy in improving environmental mastery among inmates at the Tangerang Class IIA Women’s Correctional Facility. An experimental method with a one-group pre-test and double post-test design was employed. The participants consisted of nine inmates who demonstrated low to moderate levels of psychological well-being and mindfulness. Data were analyzed using a paired-sample t-test and the N-Gain Score to evaluate changes before and after the intervention. The findings revealed a statistically significant improvement in environmental mastery following mindfulness therapy (t(8) = -12.72, p < 0.001), with the positive effects remaining evident during the follow-up assessment. The average N-Gain score of 0.546 indicated that the intervention achieved a moderate level of effectiveness. These findings suggest that mindfulness therapy is an effective and practical psychological intervention for enhancing environmental mastery, strengthening psychological adaptation, and supporting the overall well-being of inmates in correctional settings.